74 IS RIFAXIMIN EFFECTIVE TREATMENT FOR SMALL INTESTINAL BACTERIAL OVERGROWTH?. (1st January 2006) - Majewski, M.; Sostarich, S.; Foran, P.; McCallum, R. W.
Abstract : Introduction: Rifaximin is an orally administrated, nonabsorbed, nonsystemic antibiotic recently approved by the US Food and Drug Administration for traveler's diarrhea. Its utility in eradication of small intestinal bacterial overgrowth (SIBO) is currently being evaluated. Purpose: The aim of this study is to investigate efficacy and safety of rifaximin for bacterial eradication and relieving symptoms in patients affected by SIBO. Methods: Treatment with rifaximin 200 mg qid was undertaken for 4 weeks. Assessment of a symptom score consisting of frequency and severity of bloating, gas, abdominal pain, and bowel movements was calculated at the beginning and after treatment. Glucose breath test (GBT) was also performed. Standard demographics were assessed. Subjects: Ten consecutive symptomatic patients (8 F and 2 M, mean age of 53, range 19-85) were prospectively studied in an open-labeled fashion. Seven patients (70%) presented with diarrhea, 3 (30%) with bloating and gas as a dominant symptom. All patients had a > 20 ppm concentration of hydrogen and/or methane within 90 minutes of ingesting 50 g of glucose in 150 cc aqueous solution (GBT). Three subjects were exclusive methane formers, 1 methane and hydrogen, and 6 produced only hydrogen. Results: Among patients with diarrhea 5 (71%) noticed improvement of more then 50%; 2 (29%) between 25 and 50%; 1 had no response after 4 weeks of rifaximin. Among patients with bloating + gas as the main symptom: 1 (33) had improvement between 50 and 75%; 1 (33%) between 25 and 50%, and 1 (33%) had no response. Repeat GBT in 6 patients at the end of the 4 weeks showed 50% of hydrogen formers and 67% of methane producers were eradicated. No adverse effects were observed. Conclusions: This study shows that rifaximin in a dose of 200 mg qid for at least 4 weeks seems to be effective and safe treatment in reducing diarrhea and to a lesser degree gas + bloating in patients with SIBO. Further studies of follow-up breath test results and longer-term outcome are the next step in assessing this promising new therapy for SIBO.